2015
DOI: 10.5935/0004-2749.20150051
|View full text |Cite
|
Sign up to set email alerts
|

Association between visual impairment and depression in the elderly: a systematic review

Abstract: A systematic review was conducted to investigate the relationship between visual impairment and depression in the elderly. We searched electronic databases (LILACS, SciELO, MEDLINE, and Cochrane Central Register of Controlled Trials) from inception to August 2014 and researched the described references. The search strategy used the following terms: (visual impairment or blindness) and (elderly) and (depression). Of the 641 electronics, 42 works were selected in full and another 20 were identified as being poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
69
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 23 publications
(81 reference statements)
3
69
1
2
Order By: Relevance
“…Patients in this study were on anti-VEGF therapy and the great majority of them had good visual acuity and did not have visual impairment according to the WHO's criteria (40). We still found that a percentage of wAMD patients are clinically depressed and anxious within the same prevalence range found in previous studies conducted with adults with visual impairment (53)(54)(55). Additionally, we rejected our hypothesis that depression and anxiety are negatively correlated with visual acuity, which is not consistent with some previous literature suggesting that patients with lower visual acuity are more likely to suffer from depression than patients with better visual acuity (29,30).…”
Section: Discussioncontrasting
confidence: 55%
“…Patients in this study were on anti-VEGF therapy and the great majority of them had good visual acuity and did not have visual impairment according to the WHO's criteria (40). We still found that a percentage of wAMD patients are clinically depressed and anxious within the same prevalence range found in previous studies conducted with adults with visual impairment (53)(54)(55). Additionally, we rejected our hypothesis that depression and anxiety are negatively correlated with visual acuity, which is not consistent with some previous literature suggesting that patients with lower visual acuity are more likely to suffer from depression than patients with better visual acuity (29,30).…”
Section: Discussioncontrasting
confidence: 55%
“…To date, the majority of sensory loss and mental health literature has focused on VL and depression. Prior research consistently demonstrates that older adults with VL have an increased risk of depression . Possible mechanisms include a reduction in social activities and subsequent social isolation .…”
Section: Introductionmentioning
confidence: 99%
“…Prior research consistently demonstrates that older adults with VL have an increased risk of depression. [9][10][11][12][13] Possible mechanisms include a reduction in social activities and subsequent social isolation. 14,15 It has also previously been demonstrated that depression and worse mental health outcomes are observed in those with poorer mobility and physical health, [16][17][18] as well as being more common amongst women 17 and those who are less educated and unmarried or live alone.…”
Section: Introductionmentioning
confidence: 99%
“…26 Afflicted patients have an increased risk of falling, difficulty in reading, depression, and higher levels of institutionalization. [27][28][29] VFI deters the ability of patients to participate in rehabilitation, resulting in a longer recovery period. Moreover, the presence of homonymous hemianopia is related to a poor survival.…”
Section: Discussionmentioning
confidence: 99%